Combined Effect of Diaphragmatic Breathing Exercise and Pelvic Floor Exercise in Patients with Non-Specific Chronic Low Back Pain.: Life Sciences -Physiotherapy - Dangmei, Glory; Kalita, Abhijit; Dutta, Abhijit (International Journal of Life Science and Pharma Research, 2023)
Low back pain (LBP) is more of a symptom than a disease that affects people of all ages and is the leading cause of disability worldwide. Up to 85% of people experience non-specific LBP with no diagnosable underlying pathology. Therefore, healthcare research has focused on understanding the mechanisms underlying the maintenance of pain in chronic non-specific LBP (CNSLBP). We aimed to determine the combined effect of diaphragmatic breathing exercises and pelvic floor exercises in patients with non-specific chronic low back pain. It was an experimental design study, where 30 subjects, both Male and Female, with a primary diagnosis of non-specific chronic low back pain by the physician were recruited into two groups or intervention sequences with 15 subjects in each group. Group-A (Experimental group) received the moist hot pack, diaphragmatic breathing exercise (DBEx), pelvic floor muscle (PFM) exercise, and conventional back exercise. In contrast, Group B (the Control group) received a moist hot pack and conventional back exercise for five sessions per week for a total of 6 weeks. The Outcome measures used were the Visual Analog Scale (VAS) and Oswestry Disability Index (ODI). The paired 't'-test was used to analyse both groups' pre-test and post-test results. The study concluded that both Group-A (moist hot pack, diaphragmatic breathing exercise, pelvic floor exercise, and conventional back exercise) and Group-B (moist hot pack and conventional back exercise) showed improvement post-treatment and was found to be significant p < 0.05 in VAS in terms of pain and ODI in terms of disability. However, the mean score of VAS and ODI posttreatment decreased more in Group-A than in Group B. The Group-A treatment protocol resulted better in alleviating the pain and was effective in improving the disability. A suggestion to add DBEx and PFM exercises in physical therapy intervention to manage CNSLBP can be considered.